Stepping Back and Listening: Staff Experiences of Using a Coaching Approach in an Acute Rehabilitation Ward for Older Adults. (August 2016) - Gray, Debra; Ross, Kirsty; Prat-Sala, Merce; Kibble, Sharon; Harden, Beverley
Previous research has highlighted that acute care provision can lead to a loss of confidence, control, and independent functioning in older adult patients. In addition, it is recognized that interactions between patients and health care staff are central to the prevention of functional decline in patients. In this study, we aimed to affect the staff–patient relationship by implementing a coaching intervention in an older adult acute care setting. Here, we report on staff experiences of this coaching approach. Data were collected from 16 members of staff via semi-structured interviews, which were analyzed using thematic analysis. Four themes were identified: Putting a Label on It, Stepping Back and Listening, Identifying the Opportunities, and Working as Team. Our findings show that a coaching approach can be successful in getting staff to reconsider their interactions with patients and to focus on strategies that foster the independence and autonomy of older adult patients.